A noninvasive ultrasonic method for vascular input impedance determination applied in diagnosis of the carotid arteries - POWAŁOWSKI, Tadeusz (Archives of Acoustics, 2015)
In this study, a new method is presented for diagnosis of the extracranial carotid arteries, based on analysis of the vascular input impedance noninvasively determined in human common carotid arteries. The input impedance calculations were based on simultaneous measurements of the blood pressure and the blood flow using the ultrasonic Doppler and echo methods. In the analysis of the vascular input impedance a four-element model was applied, whose elements represented the vessel resistance (R_0), the peripheral resistance (R_p), the vessel compliance (C) and the inertance (L). The values of these elements were determined by computer simulation of the vascular input impedance using the input impedance of the model. The index of the optimum impedance simulation was the degree of agreement between the blood flow measured in the common carotid artery and the blood flow calculated from the input impedance of the model and the blood pressure. Preliminary clinical investigations were performed in 43 healthy persons and 9 sick patients. The obtained results indicate that the ratio between the vessel resistance (R_0) and the peripheral resistance (R_p) as determined by the proposed measurement method and analysis of the vascular input impedance can be an indicator in identification of stenosis and occlusions of the extracranial carotid arteries. The method described in the study permits identification of stenosis of the internal carotid arteries of ≥30%. The degree of the patency of the carotid arteries in sick persons was determined from X-ray arteriographic examinations, which were confirmed by surgical operations in 8 cases.